Design Of Knowledge Management System With Geographic Information System Use 5c4c Method In Telkom University Admission Directorate - Angga Hidayah Ramadhan; Luciana Andrawina; Muhammad Azani Hasibuan (eProceedings of Engineering, 2015)
Abstract Data will be as a core of the decision if it has a good treatment or process, which is process that data into information, and information into knowledge to make a wisdom or decision. Today, many companies have not realize it include Telkom University Admission Directorate as executor of Seleksi Masuk Bersama (SMB) Telkom that during the time, the workers only uses their feeling to make a decision. Whereas if it done, then that company can analyze the data to make a right decision to get a pin sales from student candidate or registrant that follow SMB Telkom as many as possible. Therefore, needs Knowledge Management System (KMS) with Geographic Information System (GIS) use 5C4C that can process that company data becomes more useful and can help make decisions. This information system can process data into information based on the pin sold data with 5C, and convert information into knowledge with 4C that has been several steps until these data can be useful to make easier to take a decision or wisdom, resolve problems, communicate, and quicker to learn to the employees have not experience and also for ease of viewing/visualization based on spatial data that equipped with GIS functionality that can be used to indicate events in each province with indicator that facilitate in this system. To make and build this system be used a Waterfall method that have several steps from system modeling, analysis, design, coding, verification, and maintenance. The system also have a function to save the tacit on the system then to be proceed into explicit in expert system based on the problems that will be found from the consequences of information. With the system each team can make a decision with same ways, structured, and the important is based on the actual event/data. Keywords: Knowledge Management System, 5C4C, Geographic Information system, Admission Directorate